ARCHITECTURE OF THE SPACE RADIATION SENSOR SATELLITE MODULE BASED ON ARTIFICIAL INTELLIGENCE - SECRIERU, Nicolae; CARBUNE, Viorel; ZADOROJNEAC, Tudor; MELNIC, Vladimir; IVANOVICI, Mihai; BERTESCU, Andrei; POPA, Stefan; KAZAK, Artur (Journal of Engineering Science (Chişinău))
This paper is dedicated to the study of the cosmic radiation and its effects on electronics, as well as methods to measure it in order to aid the elaboration of the architecture of the satellite module with space radiation sensors for classification and real-time analysis of cosmic radiation-induced fault patterns and state predictions the of electronic systems embedded in satellites. The architecture of the satellite module with an intelligent radiation sensor based on an FPGA device is proposed, which will include as radiation sensing elements arrays of various types of electronic memories (on semiconductors), both within the circuit and external nearby this circuit. A significant part of the FPGA circuit configuration consists in the development of acquisition, processing and communication procedures using structures with majoritz voting to exclude the influence of spatial radiation.